Sistem Deteksi Gerakan Kepala sebagai Kontrol Kursor Mouse dengan Metode Complementary Filter - Latief Nurrohman Alfansuri; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The development of technology makes people want to communicate with computers more natural, one way people communicate with computers is to use the mouse as an input device to control the computer, conventional mouse commonly used is less natural, especially for those who have deficiencies in the body (disability). Based on that required a system capable of controlling the mouse cursor based on the natural movement of the human body, this system which later can read the value of the head movement of the user and use as the input value to move the mouse cursor, to read the movement of the head will use MPU6050 and Arduino Nano as microcontroller, data transmissionson this system will be done wirelessly therefore will use nRF24L01 and arduino leonardo modules which will be used to control the mouse cursor. Complementary filter will be used to reduce the error value, Complementary filter will be tested by comparing with system output value without using filter. The error value generated by Complementary filter calculation is less than 2o. From corespodent testing, the system was able to obtain a good category average based on feedback from 30 users.